Major variations in Aspergillus fumigatus arising within aspergillomas in chronic pulmonary aspergillosis. Issue 4 (1st February 2013) - Howard, S. J.; Pasqualotto, A. C.; Anderson, M. J.; Leatherbarrow, H.; Albarrag, A. M.; Harrison, E.; Gregson, L.; Bowyer, P.; Denning, D. W.
Summary Aspergillomas develop from progressive layers of mycelial growth on the walls of pulmonary cavities over months. Aspergillomas are characteristic of chronic pulmonary aspergillosis and are a risk factor for azole resistance. We investigated genotypic and phenotypic alterations in Aspergillus fumigatus recovered from aspergillomas. Aspergillomas were removed from three patients (two at surgery, one at autopsy) and dissected. Overall 92 colonies of A. fumigatus were isolated. Microsatellite typing was conducted to determine genetic type. Itraconazole, voriconazole and posaconazole susceptibilities were performed. The cyp51A gene was sequenced in 22 isolates. Isolates from Patient 1 (n = 25) were azole susceptible and resistant, although all cyp51A sequences were wild type, the isolates split into two distinct clades. In Patient 2, isolates were less variable (n = 10), all were azole susceptible. In Patient 3 only azole‐resistant strains (n = 57) were isolated, with M220K or M220T Cyp51A alterations, and microevolution was indicated. Marked diversity was observed in isolates from these patients; revealing differences in azole susceptibility, mechanism of resistance and genetic type. Importantly, routine sampling from respiratory specimens proved suboptimal in all cases; azole resistance was missed (Patient 1), cultures were negative (Patient 2) and high‐level posaconazole resistance was not detected (Patient 3).